2022
DOI: 10.7717/peerj.13452
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and demography of Bufo japonicus and B. torrenticola (Amphibia: Anura: Bufonidae) influenced by the Quaternary climate

Abstract: The Quaternary climate affected the present species richness and geographic distribution patterns of amphibians by limiting their activities during the glacial period. The present study examined the phylogenetic relationships of Japanese toads (Bufo japonicus and B. torrenticola) and the demography of each lineage from the past to the present based on mitochondrial sequences and ecological niche models. Japanese toads are a monophyletic group with two main clades (clades A and B). Clade A represents B. j. form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 116 publications
(145 reference statements)
0
6
0
Order By: Relevance
“…In addition, the eye–body allometries of B. torrenticola and B. j. japonicus showed the same growth pattern, i.e., positive growth, while that of B. j. formosus showed a different type of growth, i.e., isometric growth. This difference may reflect the phylogenetic relationships of these toads: ([ B. j. japonicus and B. torrenticola ], B. j. formosus ) (Fukutani et al, 2022). However, there are few studies about the difference of the eye-body allometry in Bufo .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the eye–body allometries of B. torrenticola and B. j. japonicus showed the same growth pattern, i.e., positive growth, while that of B. j. formosus showed a different type of growth, i.e., isometric growth. This difference may reflect the phylogenetic relationships of these toads: ([ B. j. japonicus and B. torrenticola ], B. j. formosus ) (Fukutani et al, 2022). However, there are few studies about the difference of the eye-body allometry in Bufo .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, B. torrenticola breeds in running (lotic) water, such as mountainous streams (Matsui, 1975, 1976). In mitochondrial sequences and an ecological niche model, B. torrenticola forms a monophyletic clade with B. j. japonicus and B. j. formosus , and B. torrenticola has been suggested to have changed the morphology drastically in this lotic breeding habitat (Fukutani et al, 2022). This drastic change produces unique stream-adapted morphology in B. torrenticola.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous morphological analysis suggested that B. g. miyakonis was closely related to a continental population around Shanghai (Matsui, 1984). Several subsequent molecular studies have confirmed that B. g. miyakonis is a member of the B. gargarizans species group (allozyme: Nishioka et al, 1990; mitochondrial (mt) DNA: Igawa et al, 2006, Hase et al, 2012, Fukutani et al, 2022: in these studies, a few samples of the B. gargarizans species group, including B. g. miyakonis , were analyzed as out groups of B. japonicus species group). Igawa et al (2006) estimated that the divergence time between the Miyako population and its close relative, the Beijing lineage, was approximately 0.9 Ma.…”
Section: Introductionmentioning
confidence: 89%
“…Location names denoted by dots with numerals are further described in Appendix I. Nishioka et al, 1990;mitochondrial (mt) DNA: Igawa et al, 2006, Hase et al, 2012, Fukutani et al, 2022 in these studies, a few samples of the B. gargarizans species group, including B. g. miyakonis, were analyzed as out groups of B. japonicus species group). Igawa et al (2006) estimated that the divergence time between the Miyako population and its close relative, the Beijing lineage, was approximately 0.9 Ma.…”
Section: Introductionmentioning
confidence: 99%